2016
DOI: 10.1038/srep28301
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-203 suppresses cell proliferation, migration and invasion in colorectal cancer via targeting of EIF5A2

Abstract: While it is known that miR-203 is frequently downregulated in many types of human cancer, little is known regarding its expression and functional role in colorectal cancer (CRC). In this study, we aimed to investigate the expression and the potential mechanisms of miR-203 in colorectal cancer. MiR-203 was significantly downregulated in CRC tissues compared with matched normal adjacent tissues. Our clinical data show that decreased miR-203 was associated with an advanced clinical tumor-node-metastasis stage, ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 37 publications
(55 reference statements)
1
61
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a subset of non-coding RNAs of ~19-23 nucleotides in length, which post-transcriptionally regulate gene expression (5). miRNAs play a role in crucial biological processes including proliferation (6,7), differentiation (8), chemosensitivity (9,10) and apoptosis (11,12). Studies have shown that aberrations in the expression of certain miRNAs may cause or contribute to human diseases, including cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a subset of non-coding RNAs of ~19-23 nucleotides in length, which post-transcriptionally regulate gene expression (5). miRNAs play a role in crucial biological processes including proliferation (6,7), differentiation (8), chemosensitivity (9,10) and apoptosis (11,12). Studies have shown that aberrations in the expression of certain miRNAs may cause or contribute to human diseases, including cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated expression of WHSC1 is often observed in many types of human cancers, and expression product of WHSC1 is essential for the growth of cancer cells [52][53][54] . The gene EIF5A2 was related to not only ESCA [55][56][57] , but also breast cancer 58 , lung cancer 59,60 , bladder cancer 61,62 , stomach cancer [63][64][65] , oral cancer 66 , liver cancer 67 , and colorectal cancer 68 . By checking the expression of these genes detected in tumors (RNA-seq data in TCGA), most of these genes are significantly up-regulated in tumors ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used to amply the 3′‐UTR of SOX2 were designed and synthesized by Sangong (Shanghai, China). The mutagenesis of the 3′‐UTR segment of SOX2 was performed as previously described . Both wild‐type and mutant luciferase reporter constructs were confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The mutagenesis of the 3′-UTR segment of SOX2 was performed as previously described. 34 Both wild-type and mutant luciferase reporter constructs were confirmed by sequencing. GBM cells were transiently cotransfected with 0.2 μg of pGL3-SOX2-3′-UTR or pGL3-SOX2-3′-UTR Mut, 0.02 μg of pRL-TK-Renilla luciferase reporter plasmids (Promega) containing the Renilla luciferase for normalization and with 5 pmol of miR-429 mimic or negative control.…”
Section: Bioinformatics and Luciferase Reporter Assaymentioning
confidence: 99%